2022
DOI: 10.24198/agrikultura.v32i3.35777
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Inokulum dalam Semi Ko-Enkapsulasi Sel Lactobacillus acidophilus Menggunakan Enkapsulan Matriks Eucheuma cottonii – Maltodekstrin

Abstract: Media inokulum berfungsi untuk meningkatkan jumlah sel Lactobacillus acidophilus sebelum dienkapsulasi. Media inokulum dapat turut berperan dalam mempertahankan jumlah atau viabilitas sel selama proses enkapsulasi. Tujuan penelitian ini adalah mengkaji pengaruh media inokulum dalam proses enkapsulasi sel BAL L. acidophilus dalam matriks semi ko-enkapsulasi Eucheuma cottonii – maltodekstrin menggunakan metode pengeringan beku dan metode pengeringan semprot. Metode penelitian yang digunakan adalah deskriptif. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Based on the results of Hayami's analysis, positive added value means that the development of RTD prebiotic candidate milk formulations can provide added value for business owners. Based on the observations in Tables 5 and 6 of the economic added value of the RPM and RFM treatment, it can be concluded that the economic added value is strongly influenced by raw materials, product yield, and prices resulting from raw materials composition differences [19] [16]- [18], [21]. The addition of raw materials or differences in the composition of the raw material can increase the product yield as well as the value of the products produced.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of Hayami's analysis, positive added value means that the development of RTD prebiotic candidate milk formulations can provide added value for business owners. Based on the observations in Tables 5 and 6 of the economic added value of the RPM and RFM treatment, it can be concluded that the economic added value is strongly influenced by raw materials, product yield, and prices resulting from raw materials composition differences [19] [16]- [18], [21]. The addition of raw materials or differences in the composition of the raw material can increase the product yield as well as the value of the products produced.…”
Section: Resultsmentioning
confidence: 99%